Solution-processible Cd-doped ZnO nanoparticles as an electron transport layer to achieve high performance polymer solar cells through improve conductivity and light transmittance. (13th October 2019) - Li, Jianfeng; Ren, Meiling; Qing, Jicheng; Wang, Yufei; Liang, Zezhou; Wang, Ningning; Tong, Junfeng; Yang, Chunyan; Xia, Yangjun
Abstract: In this work, electron transport layers (ETLs) with high charge transfer ability were prepared by doping ZnO nanoparticles with different concentrations of cadmium(Cd). The inverted polymer solar cell based on PTB7-Th: PC71 BM as active layer and various concentrations Cd-doped ZnO (CZO) as ETLs were fabricated. The PCE of the device with optimized Cd content in the ZnO film was about 14.7% larger than that of the pure ZnO-based cells. The cadmium-doped ZnO(CZO) is a good candidate to be used as a high-quality transparent electrode in solar cell applications.